Composite films from kenaf derived cellulose (KDC) fibers and polylactic acid (PLA) - Abd Rahman, Siti Hajar; A. Talib, Rosnita; Abdan, Khalina; Chin, Nyuk Ling; Yusof, Yus Aniza; Md. Yunos, Khairul Faezah (2010)
Composite films were prepared from kenaf derived cellulose fibers (KDC) and polylactic acid (PLA) resin by melt blending using an internal mixer. Cellulose was derived from kenaf via standard ASTM D1104 method. The composites were incorporated with 0 to 60 % (dry weight basis) of KDC fiber loading into PLA, then were hot pressed to produce films with thickness of 0.30 to 0.35 mm. Oxygen permeability test and Differential Scanning Calorimetry (DSC) measurement in the KDC-PLA composites were conducted. Increasing the loading of KDC (up to 60 %) in KDC-PLA films exhibited reduction of 77 % and 85 % in oxygen transmission rates (OTR) and permeation coefficient (P) respectively, as compared to neat PLA. Whereas, addition of KDC into composites has reduced the crystallinity of composites. Even though incorporation of KDC fibers has negative influence on the crystallinity of composites, the overall blocking effect of the fibers counteract this negative effect and produced better oxygen barrier as compared to the commercial PLA for packaging applications.